Manajemen Pengembangan Kompetensi Sumber Daya Aparatur Pemerintah Desa dalam Mendukung Pelayanan Publik Berbasis Digital di Kabupaten Ngawi - Khoyrul Anwar; Lina sugiyanto; Rachmawati Koesoemaningsih (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2026)
The digital transformation of public services at the village level requires adequate competencies of village government officials as the main actors in implementing the Electronic-Based Government System. This study aims to analyze the management of competency development of village government officials in supporting digital-based public services through a case study of the implementation of the SRIKANDI and SRIGATI applications in Ngawi Regency, Indonesia. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the management of competency development among village officials has not been implemented strategically and sustainably. Competency planning is not based on actual needs, implementation remains formalistic and oriented toward short-term technical training, and evaluation is not linked to performance outcomes or the impact of digital public services. As a result, the utilization of digital services tends to be administrative in nature and has not been optimal in creating public value. This study emphasizes that strengthening the strategic management of competency development is a fundamental prerequisite for the successful digital transformation of village-level public services within the digital governance framework